IMPLEMENTASI PERATURAN DAERAH KABUPATEN JEMBER NOMOR 6 TAHUN 2008 (TERHADAP MARAKNYA PEDAGANG KAKI LIMA DI SEPANJANG JALAN JAWA) - Agustini, Amalia; Hamdi HS, Hamdi HS (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2025)
The presence of street vendors (PKL) along Jalan Jawa, Jember Regency, has provided economic benefits for the lower class, but has also caused various problems, such as traffic jams, cleanliness, and public order. The Jember Regency Government has implemented Regional Regulation (Perda) Number 6 of 2008 to regulate and discipline street vendors, but its implementation still faces many obstacles. This study aims to analyze the effectiveness of the regulation, the obstacles faced in its implementation, and the solutions that can be applied to achieve a balance between the economic needs of street vendors and the arrangement of public space. The results of the study indicate that the lack of socialization, limited strategic relocation locations, weak supervision, and community dependence on the informal sector are the main factors that hinder the implementation of the regulation. Therefore such as providing suitable alternative locations, empowering street vendors, and coordination between agencies to create more effective policies.